Storm surge modeling in the Philippine setting using ADCIRC+SWAN through parallel computing - Rayo, Joshua Frankie; Jacinto, Ryan Anthony; Esguerra, Tricia Mae; Bongolan, Vena Pearl (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The Philippines is uniquely very achipelagic, and, relatively, the Philippines experience a higher number of typhoons. Consequently, devastating storm surges occured all over the country, though it is only through the recent Typhoon Yolanda that it is once more brought to common knowledge. No model nor software has been tailored specifically for the Philippine setting to measure storm surges that occur every time a typhoon is in the country. Thus, the researchers are tailoring a model specifically for the Philippines and designing it to compute fast enough to be able to give real-time storm surge predictions around the country. The model being used for this is the ADCIRC (ADvanced Multi-Dimensional CIRCulation) model couple with SWAN (Simulating WAves nearshore) model. The SWAN model employs an analog of the Gauss-Seidel sweeping method, while the ADCIRC model employs a continuous-Galerkin solution of the Generalized Wave Continuity Equation. In order to not sacrifice accuracy for speed which was designed for real-time use, the use of parallel computing was employed so as to be able to more efficiently compute using the model. This was done through a 10-node parallel computer network through a Beowulf cluster built using 10 units of used AMD64 boxes (Intel x86_64 architecture).
Thesis (B.S. Computer Science)--University of the Philippines Diliman
Keywords: Storm surges -- Mathematical models. -- Philippines